2013
DOI: 10.1056/nejmoa1213557
|View full text |Cite
|
Sign up to set email alerts
|

Faldaprevir and Deleobuvir for HCV Genotype 1 Infection

Abstract: BACKGROUND: Interferon-free regimens would be a major advance in the treatment of patients with chronic hepatitis C virus (HCV) infection. METHODS: In this phase 2b, randomized, openlabel trial of faldaprevir (a protease inhibitor) and deleobuvir (a nonnucleoside polymerase inhibitor), we randomly assigned 362 previously untreated patients with HCV genotype 1 infection to one of five groups: faldaprevir at a dose of 120 mg once daily and deleobuvir at a dose of 600 mg three times daily, plus ribavirin, for 16,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
176
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 211 publications
(192 citation statements)
references
References 27 publications
12
176
1
3
Order By: Relevance
“…In addition to the results presented here, faldaprevir has shown efficacy as part of an interferon-based regimen for treatment-experienced patients (STARTVerso3) [33], and as part of an interferon-free regimen [34]. Regional differences in the cost of HCV therapies may lead to continued use of interferon-based regimens for the foreseeable future.…”
Section: Discussionmentioning
confidence: 79%
“…In addition to the results presented here, faldaprevir has shown efficacy as part of an interferon-based regimen for treatment-experienced patients (STARTVerso3) [33], and as part of an interferon-free regimen [34]. Regional differences in the cost of HCV therapies may lead to continued use of interferon-based regimens for the foreseeable future.…”
Section: Discussionmentioning
confidence: 79%
“…Safer and more effective HCV regimens may improve the prognosis of C-HCC. [34][35][36] A previous study also revealed the improved prognosis of B-HCC over time. However, that study included patients treated with surgery, ablation therapies and TACE.…”
Section: Discussionmentioning
confidence: 89%
“…These results indicated that CC genotype was associated with SVR. In that way, Zeuzem et al [51] recorded that the CC variant of rs12979860 was associated with increased likelihood of achieving SVR in comparison with non-CC variants. Consequently, the CC variant of SNP rs12979860 is the strongest genetic pretreatment predictor of SVR in HCV-G1 and G4 patients [21,28] …”
Section: Citationmentioning
confidence: 99%